Multiple Directing Visions Of One Subject In Cinematic Discourse, The Films 11 Of September As A Model - Amansef, Adnan Kazem (Turkish journal of computer and mathematics education, 2021)
The September 11 incident is a cosmic event with distinction, which caused many filmmakers and those interested in cinematic affairs to try to produce films about this incident, and because the incident was treated or viewed from multiple perspectives, the researcher found that there was a need to address the external vision of each director and explain artistic and stylistic essences The aesthetic of each of them, so he chose a title for his research to be represented in the following: Multiple visions to direct one subject in cinematic discourse, the films of September 11 as a model ,The current research included four chapters, the first of which contained the problem of the research and its importance, and it was crystallized from the question: How are there multiple directives in dealing with one subject in the cinematic discourse? As for the second chapter, it was divided into two topics, the first topic includes the September 11 incident, and the second topic dealt with the diversity and multiplicity of external visions of how to deal with one topic, so that the chapter ends in its entirety from the indicators that informed the researcher in defining his research tool and analyzing samples, while the third chapter included research procedures This includes the research community, the nature of sample selection in it and the analysis of the sample, while the fourth chapter includes results, conclusions and sources.